ВЛИЈАНИЕ НА ВИСОКИТЕ ТЕМПЕРАТУРИ ВРЗ АСФАЛТНИТЕ СЛОЕВИ НА КОЛОВОЗНИТЕ КОНСТРУКЦИИ ВО ГРАД СКОПЈЕ - Тасевска Маџовски, M., Мијоски, Г. (Macedonian Association of Road Engineers "Via Vita", 2019)
The pavement structures of roads, as part of the road network, represent the most expensive and most exposed part of the road from which depends the comfort and safety of driving, time spent on travel, but also the size of the total costs for transport that is also indirectly dependent. In the Republic of N. Macedonia there is a large temperature range over the year, which can be said that reaches more than 60˚C. Therefore, it is of great importance to choose the appropriate type of asphalt mix, ie the type of bitumen that will give an adequate response to these temperature differences, that would extend the period to subsequent rehabilitation and optimize the financial resources invested in road infrastructure. According to the performed measurements and analyzed data, for the region of Skopje, only the maximum bitumen application temperature is defined, because only the maximum temperatures are considered.
Keywords: Asphalt mixture, bitumen, road construction, maximal temperatures